111 Returns to Operating Room After Neurosurgical Procedures in a Tertiary Care Academic Medical Center: Implications for Health Care Policy and Quality Improvement. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Kerezoudis, Panagiotis; Glasgow, Amy E; Alvi, Mohammed A; Spinner, Robert J; Goyal, Anshit; Meyer, Fredric B; Bydon, Mohamad; Habermann, Elizabeth B
Abstract: INTRODUCTION: Return to the operating room (ROR) has been put forth by the National Quality Forum and the American College of Surgeons as a surgical quality indicator. However, current quality metrics fail to consider the nature and etiology of the ROR. The objective of the study is to provide a comprehensive description of all reoperations after neurosurgical procedures and assess the validity of ROR as a quality measure in neurosurgery. METHODS: We retrospectively analyzed all neurosurgical procedures (cranial, spinal, peripheral, or combined) performed in a high-volume, tertiary care academic medical center between June 1, 2014 and December 31, 2016. Based on a system constructed and validated at our institution, we classified RORs as follows: (a) unplanned related return to the OR, (b) planned return due to complications, (c) planned staged return, or (d) unrelated return. Identified RORs were further validated by manual chart review. RESULTS: A total of 9200 unique neurosurgical cases (cranial—5133, spinal—3265, peripheral—802) were identified, of which 785 had an ROR within 45 d (8.5%). Among these patients, there were 788 RORs (8.6%) with an average of one ROR per patient (range: 1-2). Median time to ROR (interquartile range) was 9 d (4-15). Specifically, 4.2% (n = 392) were planned staged returns, 3.4% (n = 309) were unplanned, 0.3% (n = 30) were unrelated, and 0.6% (n = 57) were planned because of previous complications. Cranial procedures had the highest unplanned ROR rate (4.2%), followed by spinal (2.8%) and peripheral nerve (0.4%). The most common reason for an unplanned ROR was wound complication/surgical site infection (SSI) (n = 106, 34.3%), followed by hematoma evacuation (n = 43, 13.9%) and cerebrospinal fluid (CSF) leak (n = 35, 11.3%). CONCLUSION: Unplanned RORs were relatively rare and most commonly associated with wound complication/SSI, postoperative hematoma, and CSF leak. To better reflect surgical quality, ROR metrics should indicate whether the return was planned or unrelated.